2023
DOI: 10.1002/anie.202313556
|View full text |Cite
|
Sign up to set email alerts
|

New Frontiers in Organosodium Chemistry as Sustainable Alternatives to Organolithium Reagents

David E. Anderson,
Andreu Tortajada,
Eva Hevia

Abstract: With their highly reactive respective C−Na and N−Na bonds, organosodium and sodium amide reagents could be viewed as obvious replacements or even superior reagents to the popular, widely utilised organolithiums. However, they have seen very limited applications in synthesis due mainly to poor solubility in common solvents and their limited stability. That notwithstanding in recent years there has been a surge of interest in bringing these sustainable metal reagents into the forefront of organometallics in synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
(79 reference statements)
1
3
0
Order By: Relevance
“…We hypothesize that the deprotonated BPEA derivatives have larger binding affinities for the highly electropositive Nd 3+ ions than for the Na + ions. This is in line with lanthanides being some of the most oxophilic elements in the periodic table and exhibiting higher oxophilicity than the alkali metals including sodium. , The preferential binding ensures close coupling between the energy donating organic molecules and energy accepting lanthanide ions in the LnNPs.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…We hypothesize that the deprotonated BPEA derivatives have larger binding affinities for the highly electropositive Nd 3+ ions than for the Na + ions. This is in line with lanthanides being some of the most oxophilic elements in the periodic table and exhibiting higher oxophilicity than the alkali metals including sodium. , The preferential binding ensures close coupling between the energy donating organic molecules and energy accepting lanthanide ions in the LnNPs.…”
Section: Resultssupporting
confidence: 56%
“…This is in line with lanthanides being some of the most oxophilic elements in the periodic table and exhibiting higher oxophilicity than the alkali metals including sodium. 36,37 The preferential binding ensures close coupling between the energy donating organic molecules and energy accepting lanthanide ions in the LnNPs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Remarkably, onward reactivity of intermediate organosodium compounds has even been achieved in reaction mixtures containing protic substances such as water, glycerol, deep eutectic solvents (DESs) or air, all generally nemeses of polar organometallic compounds 18 . A selection of these and other recent advances has been captured in a mini review 19 .…”
Section: Introductionmentioning
confidence: 99%
“…In parallel to these studies, within polar organometallic chemistry there has been a renaissance on applications of organosodium reagents in organic synthesis [10a,b] . Studies by the groups of Asako and Takai have shown the potential of using Na dispersions to generate arylsodium species in situ that can subsequently be functionalised via Pd catalysed cross‐coupling reactions [11a,b] .…”
Section: Introductionmentioning
confidence: 99%